2012
DOI: 10.1111/j.1532-849x.2012.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Dimensional Finite Element Analysis for Overdenture Attachments Supported by Teeth and/or Mini Dental Implants

Abstract: Three freestanding mini dental implants with flexible acrylic attachment systems supporting an overdenture were better choices than four mini dental implants with O-ring attachment systems, which showed the maximum flexing and stress values in this qualitative comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Therefore, vertical bone in the present study was close from expected bone loss at first year and even in the years after. 3,11,15,26,28 However, more bone loss was expected after the first year especially in this smokers' cohort and at 5 years of overdenture service. The present results could be claimed to the frequent maintenance and follow-up which was essential to keep bone loss within the acceptable limit.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, vertical bone in the present study was close from expected bone loss at first year and even in the years after. 3,11,15,26,28 However, more bone loss was expected after the first year especially in this smokers' cohort and at 5 years of overdenture service. The present results could be claimed to the frequent maintenance and follow-up which was essential to keep bone loss within the acceptable limit.…”
Section: Discussionmentioning
confidence: 82%
“…These findings coincide with several studies. 12,[28][29][30] For example, Fatalla et al, 28 confirmed the influence of mini implant number and location on the amount of stress expected. They found higher stress values on the posterior implants than anterior implants in the parasymphyseal area.…”
Section: Discussionmentioning
confidence: 89%
“…Remaining two studies employed attachments of different elastic modulus; no difference was present in between attachment types. 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Excluded studies have been mentioned in ( Table 1 ). Total ten studies from five different countries were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Prakash V et al (2009) 41 Used only different number of bar attachment systems 9. Fatalla et al (2012) 42 Used teeth as an abutment in one model 10. Barao et al (2013) 43 Compared between implant supported fixed prosthesis and implant retained overdentures.…”
Section: Resultsmentioning
confidence: 99%
“…В них рас-сматриваются проблемы моделирования отдельно стоящего имплантата в челюсти (без протеза) [10][11][12], либо описана установка имплантатов на беззубой челюсти с использованием упрощенной геометрии протеза [13,14]. Вместе с тем на этапе планирования ле-чения и контроля остеоинтеграции имплантатов стоматологи все ча-ще используют компьютерную томографию, которая позволяет со-здавать более сложную геометрию конструкции и рассматривать весь этап планирования лечения, начиная с установки временных проте-зов на временных имплантатах и заканчивая фиксацией постоянных ортопедических конструкций.…”
unclassified